Fluorocarbon functionalized MXene-based materials for detecting plant viruses, preparation and detection methods
By using fluorocarbon function MXENE base composite materials, the problem of low accuracy of plant virus RNA detection in existing technologies is solved, and the efficient enrichment and extraction of plant virus RNA is realized, and the accuracy of detection is improved.
Patent Information
- Application Number
- CN202411420013.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-12
- Publication Date
- 2025-01-24
- Estimated Expiration
- 2044-10-12
AI Technical Summary
Existing plant virus RNA detection methods are difficult to fully enrich and extract plant virus RNA, resulting in low detection accuracy.
Fluorocarbon functionalized MXene-based composite material is used, which is composed of a magnetic MXene composite structure, a polydopamine layer and a fluorocarbon compound. Through the interaction of these components, efficient enrichment and extraction of plant virus RNA can be achieved.
Improve the detection accuracy of the plant virus RNA, enhance the adsorption capacity of the composite material on RNA, and simply achieve the enrichment, extraction and release of RNA.
Smart Images

Figure CN118925695B_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the field of analytical chemistry, and in particular, relates to fluorocarbon functionalized MXene-based materials for detecting plant viruses, and preparation and detection methods thereof. Background Art
[0002] Viruses are the most genetically diverse organisms that cause infections in plants, animals, and humans. In general, viruses consist of a small genome that encodes only a few proteins, which makes it difficult to control viruses using a variety of methods. Among plants, plant viral diseases are the second largest plant disease and pose a huge risk to agricultural production. It is reported that viruses cause about half of emergency infectious diseases in various crops, and viral infections cause about 40% of total crop losses. In 2019, the International Committee on Taxonomy of Viruses confirmed 1,484 plant viruses, and pathogenic virus species accounted for almost half of plant pathogenic microorganisms. Among them, more than 90% of plant viruses are RNA viruses, which are usually transmitted through insect vectors, agricultural tools, and other direct or external forms of contamination. They have a fast onset and great harm, significantly reducing the quality and quantity of food crops, becoming one of the main constraints on global agricultural production. Therefore, the rapid and effective identification of plant viral RNA and the establishment of accurate detection methods are of great significance for risk warning of plant and animal biosafety in the agricultural field. However, the existing detection methods of plant viral RNA are difficult to fully enrich and extract plant viral RNA, and the detection accuracy is low.
[0003] It should be noted that this part of the present invention only provides background technology related to the present invention and does not necessarily constitute prior art or known technology. Summary of the invention
[0004] The purpose of the present invention is to overcome the defects of existing plant virus RNA detection methods, which are difficult to fully enrich and extract plant virus RNA and have low detection accuracy, and to provide fluorocarbon functionalized MXene-based materials, preparation and detection methods for detecting plant viruses. The fluorocarbon functionalized MXene-based composite material, when used to detect plant virus RNA, can fully enrich and extract plant virus RNA and improve detection accuracy.
[0005] In order to achieve the above-mentioned objectives, in a first aspect, the present invention provides a fluorocarbon functionalized MXene-based composite material for plant virus RNA detection, comprising a magnetic MXene composite structure, a polydopamine layer coated on the surface of the magnetic MXene composite structure, and a fluorocarbon compound attached to the surface of the polydopamine layer, a MXene layered matrix and magnetic nanoparticles attached to the MXene layered matrix constitute the magnetic MXene composite structure, the magnetic nanoparticles are attached between the layers of the MXene layered matrix and / or on the outer surface of the MXene layered matrix, and the fluorocarbon compound includes a surfactant with a fluorocarbon chain as a non-polar group.
[0006] In some preferred embodiments, the magnetic nanoparticles are uniformly attached to the outer surface and between the layers of the MXene layered matrix.
[0007] In some preferred embodiments, the magnetic response intensity of the fluorocarbon functionalized MXene-based composite material is 10 emu / g-50 emu / g; and / or, based on the total weight of the fluorocarbon functionalized MXene-based composite material, the weight proportion of fluorine element is 0.5 wt%-10 wt%.
[0008] In some preferred embodiments, the fluorocarbon compound is selected from at least one of FS34, FS50, FS61, FS3000, and FS3100; and the magnetic nanoparticles are selected from at least one of ferroferric oxide nanoparticles and spinel ferrite nanoparticles.
[0009] Preferably, the fluorocarbon compound includes FS61, the MXene layered matrix includes titanium carbide, and the magnetic nanoparticles include ferrosoferric oxide nanoparticles.
[0010] In a second aspect, the present invention provides a method for preparing the fluorocarbon functionalized MXene-based composite material described in the first aspect, comprising: attaching magnetic nanoparticles on a MXene layered matrix to obtain a magnetic MXene composite material, coating a polydopamine layer on the surface of the magnetic MXene composite material to obtain a magnetic MXene composite material with surface polydopamine functionalized, attaching a fluorocarbon compound on the surface of the polydopamine layer to obtain the fluorocarbon functionalized MXene-based composite material, wherein the fluorocarbon compound is a surfactant having a fluorocarbon chain as a non-polar group.
[0011] In some preferred embodiments, the preparation of the magnetic MXene composite material includes: mixing a metal salt, a weak acid and a strong base salt, a polyol polymer and a MXene layered matrix in a polyol, and obtaining the magnetic MXene composite material through a solvothermal reaction.
[0012] Preferably, the preparation of the magnetic MXene composite material further comprises: the metal salt is anhydrous ferric chloride, the weak acid and strong base salt is anhydrous sodium acetate, the polyol polymer is polyethylene glycol, and the polyol is ethylene glycol; anhydrous ferric chloride, anhydrous sodium acetate, polyethylene glycol and MXene layered matrix are mixed in a mass ratio of (1-3): (2-5): 1: (0.5-3), and 10 mL-35 mL of ethylene glycol is used for each gram of anhydrous ferric chloride;
[0013] The reaction temperature of the solvent thermal reaction is 160° C.-220° C., and the reaction time is 6 h-12 h.
[0014] In some preferred embodiments, the preparation of the magnetic MXene composite material functionalized with surface polydopamine comprises: mixing the magnetic MXene composite material and dopamine in a buffer solution, stirring and reacting at a temperature of 20° C. to 50° C. for 24 h to 72 h, and self-polymerizing dopamine on the surface of the magnetic MXene composite material to coat a polydopamine layer, thereby obtaining the magnetic MXene composite material functionalized with surface polydopamine;
[0015] The pH of the buffer solution is 7-9, the magnetic MXene composite material and dopamine are mixed in a mass ratio of 1:(0.5-5), and the buffer solution is a Tris-HCl buffer.
[0016] In some preferred embodiments, the process of attaching the fluorocarbon compound includes: mixing the surface polydopamine functionalized magnetic MXene composite material and the fluorocarbon compound in water, stirring the reaction at a temperature of 20°C to 50°C for 0.5h-5h; the fluorocarbon compound and the surface polydopamine functionalized magnetic MXene composite material are mixed in a mass ratio of 1: (0.1-3).
[0017] Preferably, a fluorocarbon compound is dissolved in water to obtain a fluorocarbon compound solution, the surface polydopamine functionalized magnetic MXene composite material is dispersed in water to obtain a first dispersion, and the first dispersion is added to the fluorocarbon compound solution to mix the surface polydopamine functionalized magnetic MXene composite material and the fluorocarbon compound in water.
[0018] In a third aspect, the present invention provides a method for detecting plant virus RNA, comprising incubating a plant virus sample to be detected in a lysis solution and an acidic extraction solution at room temperature to obtain an incubated liquid, adding the fluorocarbon functionalized MXene-based composite material described in the first aspect and / or the fluorocarbon functionalized MXene-based composite material prepared by the preparation method described in the second aspect to the incubated liquid, mixing thoroughly to obtain a second dispersion, separating the second dispersion by an external magnetic field to obtain a fluorocarbon functionalized MXene-based composite material adsorbed with RNA, reverse transcribed the RNA into DNA, and performing PCR amplification after reverse transcription, wherein the reverse transcription of the RNA into DNA is to directly reverse transcribe the RNA on the fluorocarbon functionalized MXene-based composite material, or to release the RNA from the fluorocarbon functionalized MXene-based composite material to obtain an RNA dispersion, and reverse transcribe the RNA in the RNA dispersion.
[0019] In some preferred embodiments, the pH of the acidic extract is 3-7, and the acidic extract contains NaCl, dithiothreitol and PEG, wherein the concentration of NaCl is 0.5mol / L-6mol / L, the concentration of dithiothreitol is 10mmol / L-200mmol / L, and the volume fraction of PEG is 5%-50%.
[0020] In some preferred embodiments, the fluorocarbon functionalized MXene-based composite material adsorbed with RNA is dispersed in ethanol, and a third dispersion is obtained after sufficient mixing. The third dispersion is subjected to solid-liquid separation to obtain a solid phase, and the solid phase is sufficiently mixed with a Tris-HCl buffer having a pH of 8 to 9 and then separated by an external magnetic field to obtain the RNA dispersion.
[0021] The fluorocarbon functionalized MXene-based composite material of the present invention comprises a magnetic MXene composite structure consisting of a MXene layered matrix and magnetic nanoparticles attached to the MXene layered matrix, the surface of the magnetic MXene composite structure is coated with a polydopamine layer, the surface of the polydopamine layer is attached with a fluorocarbon compound, and the fluorocarbon compound comprises a surfactant having a fluorocarbon chain as a non-polar group. On the one hand, under acidic conditions, the hydrophilic group of the fluorocarbon compound combines with the phosphate backbone in RNA, and the fluorocarbon compound and RNA form a complex through a salt bridge, which can improve the adsorption, enrichment and extraction ability of the composite material for RNA; on the other hand, the surface of the MXene layered matrix has surface functional groups such as -F, -OH and -O, and polydopamine has surface functional groups such as benzene ring structure, -OH, -NH2, -NH-, etc. The surface functional groups such as -F, -OH and -O of the MXene layered matrix exposed on the surface of the composite material and the surface functional groups such as benzene ring structure, -OH, -NH2, -NH- of polydopamine can improve the adsorption, enrichment and extraction ability of the composite material for RNA through π-π action and non-covalent bond forces such as hydrogen bonds. Through the formation of a complex and non-covalent bond forces between the fluorocarbon compound and RNA through a salt bridge, the composite material can have excellent adsorption capacity for RNA, can fully enrich and extract plant virus RNA, and has high enrichment efficiency. When used to detect plant virus RNA, it can improve the detection accuracy. In addition, the MXene layered matrix material has a large specific surface area, many exposed functional groups such as -F, -OH and -O, and a large amount of coated polydopamine and attached fluorocarbon compounds, which can increase the adsorption capacity and promote the enrichment and extraction of plant viral RNA.
[0022] The polydopamine coating layer of the present invention can not only provide a benzene ring structure, -OH, -NH2, -NH- and other surface functional groups to improve the adsorption, enrichment and extraction capabilities of RNA, but also improve the chemical stability of magnetic nanoparticles and MXene. At the same time, the polydopamine coating can also improve the binding efficiency of fluorocarbon compounds on the surface of the composite material, increase the binding concentration of fluorocarbon compounds on the surface of the composite material, and thus effectively increase the composite material's ability to enrich and extract the target RNA.
[0023] The attachment of the magnetic nanoparticles of the present invention makes it easy to separate the fluorocarbon functionalized MXene-based composite material adsorbed with RNA. The fluorocarbon functionalized MXene-based composite material adsorbed with RNA of the present invention can be directly reverse transcribed and PCR amplified to detect RNA. Fluorocarbon compounds are attached to the surface of the composite material. Changing the pH of the composite material dispersion can flip the hydrophilic and hydrophobic groups of the fluorocarbon compounds, release RNA, and obtain RNA dispersion. The RNA in the RNA dispersion is reversed and PCR amplified, and RNA can also be detected. On the one hand, the RNA in the RNA dispersion is reversed, and the reverse transcription is more sufficient, and the detection accuracy of RNA is higher. On the other hand, after the RNA is released, the RNA dispersion is obtained and the fluorocarbon functionalized MXene-based composite material is obtained at the same time, and the material can be reused.
[0024] The released independent RNA of the present invention also provides a material basis for further in-depth and accurate analysis and detection of RNA. The fluorocarbon functionalized MXene-based composite material of the present invention can easily and quickly achieve RNA enrichment, extraction and release by adjusting the pH of the dispersion.
[0025] The composite material prepared by the preparation method of the present invention comprises a magnetic MXene composite structure composed of a MXene layered matrix and magnetic nanoparticles attached to the MXene layered matrix, the surface of the magnetic MXene composite structure is coated with a polydopamine layer, the surface of the polydopamine layer is attached with a fluorocarbon compound, and when used for detecting plant virus RNA, the plant virus RNA can be fully enriched and extracted through the formation of a complex through a salt bridge between the fluorocarbon compound and the RNA and the force in the form of a non-covalent bond, and the enrichment efficiency is high, and the detection accuracy can be improved, and the enrichment, extraction and release of RNA can be simply and quickly achieved by adjusting the pH of the composite material dispersion, and in the process of RNA enrichment and extraction, the composite material adsorbed with RNA is easily separated. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the drawings required for use in the embodiments are briefly introduced below. It should be understood that the following drawings only show certain embodiments of the present invention and therefore should not be regarded as limiting the scope. For ordinary technicians in this field, other related drawings can be obtained based on these drawings without creative work.
[0027] Figure 1 This is a scanning electron microscope image of the fluorocarbon functionalized MXene-based composite material of Example 1 of the present invention.
[0028] Figure 2 This is the element distribution diagram of the fluorocarbon functionalized MXene-based composite material of Example 1 of the present invention.
[0029] Figure 3 This is a spectrum characterized by X-ray photoelectron spectroscopy of the fluorocarbon functionalized MXene-based composite material of Example 1 of the present invention. DETAILED DESCRIPTION
[0030] The endpoints and any values of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of each range, the endpoint values of each range and the individual point values, and the individual point values can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.
[0031] The inventors of the present invention have found through research that the existing methods for detecting plant viral RNA are difficult to fully enrich and extract plant viral RNA, and the detection accuracy is low.
[0032] In this regard, in a first aspect, the present invention provides a fluorocarbon functionalized MXene-based composite material for plant virus RNA detection, comprising a magnetic MXene composite structure, a polydopamine layer coated on the surface of the magnetic MXene composite structure, and a fluorocarbon compound attached to the surface of the polydopamine layer, a MXene layered matrix and magnetic nanoparticles attached to the MXene layered matrix constitute the magnetic MXene composite structure, the magnetic nanoparticles are attached between the layers of the MXene layered matrix and / or on the outer surface of the MXene layered matrix, and the fluorocarbon compound includes a surfactant with a fluorocarbon chain as a non-polar group.
[0033] The fluorocarbon functionalized MXene-based composite material of the present invention comprises a magnetic MXene composite structure with magnetic nanoparticles attached to a MXene layered matrix, the surface of the magnetic MXene composite structure is coated with a polydopamine layer, the surface of the polydopamine layer is attached with a fluorocarbon compound, and the fluorocarbon compound comprises a surfactant with a fluorocarbon chain as a non-polar group. In the first aspect, under acidic conditions, the hydrophilic group of the fluorocarbon compound combines with the phosphate backbone in RNA, and a complex is formed between the fluorocarbon compound and RNA through a salt bridge, which can enhance the adsorption, enrichment and extraction ability of the composite material for RNA. In the second aspect, there is a situation where there is no fluorocarbon compound attached to part of the surface of the polydopamine layer, and the polydopamine layer is exposed on the surface of the fluorocarbon functionalized MXene-based composite material, and there is a situation where after the fluorocarbon compound is attached, part of the functional groups of the polydopamine layer are exposed on the surface of the fluorocarbon compound, that is, the surface of the fluorocarbon functionalized MXene-based composite material. Polydopamine has a benzene ring structure, -OH, -NH2, -NH- and other surface functional groups, and the benzene ring structure, -OH, -NH2, -NH2 of the polydopamine exposed on the surface of the composite material, - and other surface functional groups, which can enhance the composite material's ability to adsorb, enrich and extract RNA through the action of non-covalent bonds such as π-π interaction and hydrogen bonds; thirdly, there is a situation where part of the surface of the MXene layered matrix is not coated with a polydopamine layer and is not attached with fluorocarbon compounds, and there is a situation where part of the functional groups of the MXene layered matrix is exposed on the surface of the fluorocarbon compound, that is, the surface of the fluorocarbon-functionalized MXene-based composite material. The surface of the MXene layered matrix has surface functional groups such as -F, -OH and -O. The exposed surface functional groups such as -F, -OH and -O of the MXene layered matrix on the surface of the composite material can enhance the composite material's ability to adsorb, enrich and extract RNA through the action of non-covalent bonds such as hydrogen bonds. The MXene nanomaterial of the present invention can promote the protonation of the -COO- group on the surface of the fluorocarbon compound under acidic conditions, and the protonated -COO- combines with the negatively charged phosphate group in the phosphate skeleton in the RNA, and the various groups on the surface of the fluorocarbon functionalized MXene-based composite material form various interaction forces with the N heterocycle and -NH2, -OH, etc. in the RNA, which can improve the ability to enrich and extract plant virus RNA. Through the above-mentioned multi-faceted effects, the present invention can make the composite material have excellent adsorption capacity for RNA, can fully enrich and extract plant virus RNA, and has high enrichment efficiency. When used to detect plant virus RNA, it can improve detection accuracy.The MXene layered matrix material of the present invention has an accordion-like structure and a large specific surface area. It can uniformly attach magnetic nanoparticles between layers and on the surface to improve the separation performance of the material. At the same time, its rich functional groups such as -F, -OH and -O can be further modified to improve the application range of the material. At the same time, the large specific surface area can cover more polydopamine to form a uniform and stable protective shell layer, and further increase the loading concentration of fluorocarbon compounds, which can improve the adsorption capacity and improve the enrichment and extraction efficiency of plant virus RNA.
[0034] The polydopamine coating layer of the present invention can not only provide a benzene ring structure, -OH, -NH2, -NH- and other surface functional groups to improve the adsorption, enrichment and extraction capabilities of RNA, but also improve the chemical stability of magnetic nanoparticles and MXene. At the same time, the polydopamine coating can also improve the binding efficiency of fluorocarbon compounds on the surface of the composite material, increase the binding concentration of fluorocarbon functional compounds on the surface of the composite material, and thus effectively increase the composite material's ability to enrich and extract the target RNA.
[0035] The fluorocarbon functionalized MXene-based composite material adsorbed with RNA of the present invention can be directly reverse transcribed and PCR amplified to detect RNA. A more preferred method is to disperse the fluorocarbon functionalized MXene-based composite material adsorbed with RNA in ethanol to reduce the Na concentration in the system. Compared with the charge interaction between -CF on the surface of the nanomaterial and ethanol, -COO - The interaction with Na is greatly reduced, so that the hydrophilic and hydrophobic groups of the fluorocarbon compounds on the surface of the composite material are flipped, with the hydrophobic groups facing outward, part of the RNA is desorbed, and the solid-liquid separation is performed to obtain a solid phase of the fluorocarbon functionalized MXene-based composite material including the desorbed RNA and the RNA adsorbed. The solid phase is further mixed with Tris-HCl buffer with a pH of 8 to 9 to further reduce the interaction between RNA and -COO - The binding strength of the composite material is increased, the adsorption of RNA by the composite material is weakened, and the RNA is released completely and efficiently to obtain an RNA dispersion liquid, and the RNA in the RNA dispersion liquid is reverse transcribed and PCR amplified. On the one hand, the RNA in the RNA dispersion liquid is reverse transcribed, the reverse transcription is more sufficient, and the detection accuracy of RNA is higher. On the other hand, after the RNA is released, a fluorocarbon functionalized MXene-based composite material is obtained while obtaining an RNA dispersion liquid, and the material can be reused. In fact, the released independent RNA of the present invention also provides a material basis for further in-depth and accurate analysis and detection of RNA. The fluorocarbon functionalized MXene-based composite material of the present invention can easily and quickly achieve RNA enrichment, extraction and release by adjusting the pH of the composite material dispersion liquid.
[0036] The magnetic MXene composite structure of the present invention includes a MXene layered matrix and magnetic nanoparticles attached to the MXene layered matrix. The attachment of the magnetic nanoparticles makes it easy to separate the composite material adsorbed with RNA from the dispersion after the fluorocarbon functionalized MXene-based composite material adsorbs RNA. On the other hand, it makes it easy to separate the fluorocarbon functionalized MXene-based composite material after the RNA is released, thereby enabling simple and convenient reuse of the composite material.
[0037] The magnetic nanoparticles of the present invention are attached to the MXene layered matrix, and the magnetic nanoparticles can be attached between the lamellae of the MXene layered matrix and / or the outer surface of the MXene layered matrix. In some preferred embodiments, the magnetic nanoparticles are uniformly attached to the outer surface and between the lamellae of the MXene layered matrix. The magnetic nanoparticles are uniformly attached to the outer surface and between the lamellae of the MXene layered matrix, which can effectively increase the surface area of the MXene layered matrix material, increase the number of exposed -F, -OH and -O functional groups, increase the coating area of polydopamine and the attachment area of fluorocarbon compounds, expose many functional groups such as -F, -OH and -O, and have a large coating area of polydopamine and a large attachment area of fluorocarbon compounds, which can improve the adsorption capacity, and are more conducive to fully enriching and extracting plant virus RNA. When used to detect plant virus RNA, it is more conducive to improving the detection accuracy.
[0038] In some preferred embodiments, the magnetic response intensity of the fluorocarbon functionalized MXene-based composite material is 10 emu / g-50 emu / g; and / or, based on the total weight of the fluorocarbon functionalized MXene-based composite material, the weight (wt%) of the fluorine element accounts for 0.5wt%-10wt%. Under this preferred embodiment, the magnetic response intensity is 10 emu / g-50 emu / g, which is more conducive to the separation of the composite material adsorbed with RNA and
[0039] Reuse of composite materials; based on the total weight of the fluorocarbon functionalized MXene-based composite material, the weight (wt%) of the fluorine element accounts for 0.5wt%-10wt%, which is more conducive to fully enriching and extracting plant viral RNA, and improving the detection accuracy when used to detect plant viral RNA. The magnetic response intensity of the composite material of the present invention is, for example, 10 emu / g, 15 emu / g, 20 emu / g, 25 emu / g, 30 emu / g, 35 emu / g, 40 emu / g, 45 emu / g and 50 emu / g, and the weight of the fluorine element accounts for, for example, 0.5wt%, 1wt%, 2wt%, 3wt%, 4wt%, 5wt%, 6wt%, 7wt%, 8wt%, 9wt% and 10wt%.
[0040] In some preferred embodiments, the fluorocarbon compound is selected from at least one of FS34, FS50, FS61, FS3000, and FS3100; the magnetic nanoparticles are selected from at least one of ferroferric oxide nanoparticles and spinel ferrite nanoparticles. Under this preferred embodiment, the fluorocarbon compound is selected from FS34, FS50, FS61, FS3000, and FS3100, which can provide different chain lengths. At the same time, as a water-soluble anionic fluorosurfactant, its aqueous surface tension is low, which is more conducive to modification on the surface of polydopamine. At the same time, its low aqueous surface tension also helps to effectively enrich and extract viral RNA components from the water-soluble system, which is more conducive to fully enriching and extracting plant viral RNA. The magnetic nanoparticles are selected from ferroferric oxide nanoparticles and spinel ferrite nanoparticles, which can effectively attach to the surface and between the layers of MXene. On the one hand, it increases the surface area of the MXene layered matrix material, which is more conducive to fully enriching and extracting plant viral RNA. On the other hand, it provides excellent magnetic properties, effectively simplifies the separation process of composite materials, and is more conducive to the separation and reuse of composite materials.
[0041] Preferably, the fluorocarbon compound includes FS61, the MXene layered matrix includes titanium carbide, and the magnetic nanoparticles include ferroferric oxide nanoparticles. Under this preferred embodiment, compared with other types of fluorocarbon compounds, FS61 can achieve extremely low aqueous surface tension, is more conducive to modification on the surface of polydopamine, improves the enrichment and extraction performance of the material in the RNA extraction solution, enhances the extraction efficiency of the material, and improves the extraction and detection accuracy of RNA. The MXene layered matrix includes titanium carbide, which is composed of titanium carbide with a thickness of several atomic layers. Based on the surface-rich surface functional groups such as -F, -OH and -O and a more stable accordion-like sheet structure, it can effectively provide functionalized reaction sites and high specific surface area, which is more conducive to the modification of subsequent functional components, and can also further improve the efficiency of composite material enrichment and extraction of RNA. The magnetic nanoparticles include ferroferric oxide nanoparticles, which can improve the separation efficiency of composite materials based on excellent magnetic properties, effectively increase the reuse performance of composite materials, and are more conducive to the separation of composite materials, simplify the sample processing process, and reduce the cost of material use. Due to the structure of the composite material, magnetic nanoparticles are attached to the MXene layered matrix to form a magnetic MXene composite structure. The surface of the composite structure is coated with a polydopamine layer, and the surface of the polydopamine layer is attached with fluorocarbon compounds. Based on the extremely low aqueous surface tension of FS61, the stable accordion-like lamellar structure of titanium carbide and the rich surface functional groups such as -F, -OH and -O, the composite material can enhance its effect on the target viral RNA through electrostatic interactions and other non-covalent bond synergy, which is more conducive to its enrichment and extraction.
[0042] In a second aspect, the present invention provides a method for preparing a fluorocarbon functionalized MXene-based composite material, comprising: attaching magnetic nanoparticles on a MXene layered matrix to obtain a magnetic MXene composite material, coating a polydopamine layer on the surface of the magnetic MXene composite material to obtain a magnetic MXene composite material with surface polydopamine functionalization, and attaching a fluorocarbon compound on the surface of the polydopamine layer to obtain the fluorocarbon functionalized MXene-based composite material, wherein the fluorocarbon compound is a surfactant having a fluorocarbon chain as a non-polar group. The composite material prepared by the present invention comprises a magnetic MXene composite structure composed of a MXene layered matrix and magnetic nanoparticles attached to the MXene layered matrix, the surface of the magnetic MXene composite structure is coated with a polydopamine layer, and the surface of the polydopamine layer is attached with a fluorocarbon compound. When used for detecting plant virus RNA, the plant virus RNA can be fully enriched and extracted through the complex formed by the fluorocarbon compound and the RNA through a salt bridge and the force in the form of a non-covalent bond, and the enrichment efficiency is high, and the detection accuracy can be improved. The MXene layered matrix material has a large specific surface area, a large number of exposed functional groups such as -F, -OH and -O, and a large number of coated polydopamine and attached fluorocarbon compounds, so that the adsorption capacity can be improved, and the plant virus RNA can be fully enriched and extracted. The composite material prepared by the present invention can simply and quickly realize the enrichment, extraction and release of RNA by adjusting the pH value of the composite material dispersion. In the process of RNA enrichment and extraction, the use of magnetic nanoparticles facilitates the separation of the composite material adsorbed with RNA.
[0043] In some preferred embodiments, the preparation of the magnetic MXene composite material includes: mixing metal salts, weak acid and strong base salts, polyol polymers and MXene layered matrix in polyols, and obtaining the magnetic MXene composite material through solvothermal reaction. Under this preferred embodiment, by directly adding MXene layered two-dimensional inorganic compounds to the polyol reaction system, magnetic nanoparticles can be better formed on its surface and between layers. On the one hand, the surface area of the MXene layered matrix material is increased, which is more conducive to the full enrichment and extraction of plant virus RNA. On the other hand, a fluorocarbon functionalized MXene-based composite material with magnetic nanoparticles uniformly attached to the surface and interlayer intercalation is obtained, which is more conducive to improving the magnetic separation performance of the composite material. The present invention prepares magnetic nanoparticles through solvothermal reaction while attaching the magnetic nanoparticles to the MXene layered matrix. Compared with the pre-prepared magnetic nanoparticles, the magnetic nanoparticles are attached to the MXene layered matrix by wet stirring, ultrasonic self-assembly, etc., and the magnetic nanoparticles can be more evenly distributed on the surface and between layers of the MXene layered matrix, increasing the surface area and magnetic separation performance of the composite material, which is more conducive to enriching and extracting plant virus RNA and separating the composite material.
[0044] Preferably, the preparation of the magnetic MXene composite material also includes: the metal salt is anhydrous ferric chloride, the weak acid and strong base salt is anhydrous sodium acetate, the polyol polymer is polyethylene glycol, and the polyol is ethylene glycol; anhydrous ferric chloride, anhydrous sodium acetate, polyethylene glycol and MXene layered matrix are mixed in a mass ratio of (1-3): (2-5): 1: (0.5-3), and 10mL-35mL of ethylene glycol is used for each gram of anhydrous ferric chloride; the reaction temperature of the solvent thermal reaction is 160°C-220°C, and the time is 6h-12h. In this preferred embodiment, the metal salt is anhydrous ferric chloride, which can provide a stable iron source; the weak acid and strong base salt is anhydrous sodium acetate, which can provide acetate ions, undergo a hydrolysis reaction with trace water in the reaction system, and provide a weak alkaline environment for the reaction system, which is more conducive to the synthesis of magnetic nanoparticles; the polyol polymer is polyethylene glycol, and the polyol is ethylene glycol, which can ensure a high boiling point and high pressure conditions for the reaction system and provide a large viscosity, so that the particles are fully dispersed, which is more conducive to the formation of uniform particle size and magnetic response nanoparticles. Anhydrous ferric chloride, anhydrous sodium acetate, polyethylene glycol and MXene layered matrix are mixed in a mass ratio of (1-3): (2-5): 1: (0.5-3), which can fully ensure that the iron source in the reaction system is uniformly generated in situ in MXene, which is more conducive to improving the ability to enrich and extract plant virus RNA, and the composite material is magnetically retained. 10mL-35mL of ethylene glycol is used for each gram of anhydrous ferric chloride, which can ensure that the concentration of components in the reaction system forms a homogeneous system; the reaction temperature of the solvothermal reaction is not less than 160°C, and the reaction time is not less than 6h, which can provide sufficient reaction temperature and form a high-pressure reaction system, and can ensure sufficient reaction time for crystal nucleus growth, which is more conducive to increasing the particle size of magnetic particles, increasing the MXene interlayer spacing, and improving the overall contact area of the magnetic MXene composite material, which is beneficial to subsequent polydopamine coating and fluorocarbon compound attachment, and is beneficial to improving the ability to enrich and extract plant virus RNA. The temperature is not higher than 220°C, which is more conducive to pressure control of the reaction system.
[0045] In some preferred embodiments, the preparation of the magnetic MXene composite material functionalized with surface polydopamine includes: mixing the magnetic MXene composite material and dopamine in a buffer solution, stirring the reaction at a temperature of 20°C to 50°C for 24h-72h, and dopamine self-polymerizing on the surface of the magnetic MXene composite material to coat a polydopamine layer to obtain the magnetic MXene composite material functionalized with surface polydopamine; the pH of the buffer solution is 7 to 9, the magnetic MXene composite material and dopamine are mixed in a mass ratio of 1: (0.5-5), and the buffer solution is a Tris-HCl buffer. Under this preferred embodiment, dopamine self-polymerizes under an alkaline environment to coat the surface of the magnetic MXene composite material with a polydopamine layer. The pH of the buffer solution for dopamine self-polymerization is 7-9, which can ensure a weak alkaline environment in the reaction system and is more conducive to dopamine self-polymerization. The temperature of dopamine self-polymerization coating on the surface of the magnetic MXene composite material is not less than 20°C, which can ensure the self-polymerization effect and is more conducive to forming a uniform and stable polymer shell structure, further promoting the attachment of fluorocarbon compounds. The temperature is not higher than 50°C, which can reduce the implosion caused by the increase in temperature, and is more conducive to improving the polymerization uniformity and forming a uniform The uniform polymer shell structure further promotes the adhesion of fluorocarbons. The time is not less than 24 hours, which can fully polymerize dopamine to form a uniform and stable polymer layer, further promoting the adhesion of fluorocarbons. The mass ratio of the magnetic MXene composite material to dopamine is 1: (0.5-5), which is more conducive to forming a polymer layer with controllable shell thickness while ensuring that the magnetic MXene composite material uniformly forms a polydopamine layer, so that the composite material has suitable magnetic properties. Preferably, the buffer solution is Tris-HCl buffer, which can maintain a stable pH system to ensure sufficient self-polymerization reaction.
[0046] In some preferred embodiments, the process of attaching the fluorocarbon compound includes: mixing the surface polydopamine functionalized magnetic MXene composite material and the fluorocarbon compound in water, stirring the reaction at a temperature of 20°C to 50°C for 0.5h-5h; the fluorocarbon compound and the surface polydopamine functionalized magnetic MXene composite material are mixed in a mass ratio of 1: (0.1-3). Under this preferred scheme, the temperature of the stirring reaction is not less than 20°C, which is more conducive to ensuring that the fluorocarbon compound is fully dissolved in the reaction system and improving the reaction efficiency. The temperature is not higher than 50°C, which can maintain the mildness of the reaction system and is more conducive to ensuring the chemical stability of the composite. The time is not less than 0.5h, which is more conducive to the modification of the fluorocarbon compound on the surface of the composite material. The mass ratio of the fluorocarbon compound to the surface polydopamine functionalized magnetic MXene composite material is 1: (0.1-3), which is more conducive to sufficient fluorocarbon compound modification on the material surface and improving the material's ability to enrich and extract plant virus RNA.
[0047] Preferably, the fluorocarbon compound is dissolved in water to obtain a fluorocarbon compound solution, the surface polydopamine functionalized magnetic MXene composite material is dispersed in water to obtain a first dispersion, and the first dispersion is added to the fluorocarbon compound solution to mix the surface polydopamine functionalized magnetic MXene composite material and the fluorocarbon compound in water. The method of mixing the surface polydopamine functionalized magnetic MXene composite material and the fluorocarbon compound in water in this preferred embodiment can ensure the uniformity of the reaction system, which is more conducive to the full and uniform attachment of the fluorocarbon compound to the surface of the surface polydopamine functionalized magnetic MXene composite material. At the same time, the aqueous phase system is safe and environmentally friendly, which is more conducive to the green preparation of the composite material.
[0048] In a third aspect, the present invention provides a method for detecting plant virus RNA, comprising incubating a plant virus sample to be detected in a lysis solution and an acidic extraction solution at room temperature to obtain an incubated liquid, adding the fluorocarbon functionalized MXene-based composite material described in the first aspect and / or the fluorocarbon functionalized MXene-based composite material prepared by the preparation method described in the second aspect to the incubated liquid, mixing thoroughly to obtain a second dispersion, separating the second dispersion by an external magnetic field to obtain a fluorocarbon functionalized MXene-based composite material adsorbed with RNA, reverse transcribed the RNA into DNA, and performing PCR amplification after reverse transcription, wherein the reverse transcription of the RNA into DNA is to directly reverse transcribe the RNA on the fluorocarbon functionalized MXene-based composite material, or to release the RNA from the fluorocarbon functionalized MXene-based composite material to obtain an RNA dispersion, and reverse transcribe the RNA in the RNA dispersion. The present invention incubates the plant virus sample to be detected in a lysate and an acidic extract at room temperature, adds the aforementioned fluorocarbon functionalized MXene-based composite material, and in the process of fully mixing, the surface of the fluorocarbon functionalized MXene-based composite material fully adsorbs RNA through the binding of the hydrophilic group of the fluorocarbon compound to the phosphate backbone in the RNA and the force in the form of non-covalent bonds, thereby achieving full enrichment and extraction of the plant virus RNA, and after reverse transcription, PCR amplification can be performed to detect and analyze the virus RNA. Since the fluorocarbon functionalized MXene-based composite material of the present invention has a high adsorption capacity for RNA, the accuracy of analysis and detection can be improved.
[0049] In some preferred embodiments, the pH of the acidic extract is 3-7, and the acidic extract contains NaCl, dithiothreitol and PEG, wherein the concentration of NaCl is 0.5mol / L-6mol / L, the concentration of dithiothreitol is 10mmol / L-200mmol / L, the volume fraction of PEG is 5%-50%, and the volume ratio of the acidic extract to the lysis solution is 0.5-5. Under this preferred embodiment, the pH of the acidic extract is 3-7, which is more conducive to providing suitable acidity conditions while ensuring the stability of RNA and materials, and is more conducive to the enrichment and adsorption of viral RNA. The volume ratio of the acidic extract to the lysis solution is 0.5-5, which is more conducive to maintaining the acidity conditions and ion concentration of the system. The acidic extract contains NaCl, dithiothreitol and PEG, which can provide stable Na ions to protonate the carboxyl groups in the fluorocarbon compounds, which is more conducive to the interaction between the composite material and the RNA phosphate functional group. The concentration of NaCl is 0.5mol / L-6mol / L, which can provide sufficient ionic strength and is more conducive to the protonation efficiency of the carboxyl groups, thereby improving the enrichment and extraction ability of the material. The concentration of dithiothreitol is 10mmol / L-200mmol / L, which can reduce the RNA dimerization reaction and is more conducive to the binding efficiency of RNA and the composite material. The volume fraction of PEG is 5%-50%, which can play a role in inorganic salt solubilization and viscosity regulation, and is more conducive to improving the adsorption effect of the composite material.
[0050] In some preferred embodiments, the fluorocarbon functionalized MXene-based composite material adsorbed with RNA is dispersed in ethanol, fully mixed to obtain a third dispersion, the third dispersion is separated by solid-liquid separation to obtain a solid phase, the solid phase is fully mixed with a Tris-HCl buffer having a pH of 8 to 9, and then separated by an external magnetic field to obtain the RNA dispersion. The fluorocarbon functionalized MXene-based composite material adsorbed with RNA is dispersed in ethanol, fully mixed, the salt bridge effect is weakened, and part of the RNA is desorbed. After solid-liquid separation, a solid phase including desorbed RNA and a fluorocarbon functionalized MXene-based composite material adsorbed with RNA and a liquid phase in which non-RNA components in plant viruses are dissolved are obtained. The non-RNA components are eluted to reduce interference. The solid phase is fully mixed with a Tris-HCl buffer having a pH of 8 to 9, which can further weaken the adsorption of RNA by the composite material, achieve complete and efficient release of RNA, and the RNA in the plant virus fully enters the RNA dispersion.
[0051] The present invention is further described in detail below with reference to specific embodiments.
[0052] Example 1
[0053] A method for preparing a fluorocarbon functionalized MXene-based composite material, comprising the following steps:
[0054] Step 1: Weigh 5g of anhydrous ferric chloride, 12g of anhydrous sodium acetate, 3g of polyethylene glycol and 3g of MXene layered matrix into a beaker, and add 100mL of ethylene glycol solution. After ultrasonic dispersion, stir evenly on a magnetic stirrer at room temperature. The MXene layered matrix is a titanium carbide layered matrix. The mixed solution is then transferred to a high-pressure reactor for a solvothermal reaction, heated to 180°C for reaction, and after 12 hours of reaction, wait for it to naturally cool to room temperature, and then use an external strong magnet for adsorption and separation, and then wash with deionized water and ethanol to obtain a magnetic MXene composite material;
[0055] Step 2: Weigh 0.5 g of the magnetic MXene composite material of step 1, add 1.5 g of dopamine solid, and ultrasonically disperse in 80 mL of Tris-HCl buffer solution with a pH of 7.5. Stir the reaction at a water bath temperature of 40°C for 72 hours, and then separate it by adsorption through an external strong magnet. Dopamine self-polymerizes on the surface of the magnetic MXene composite material to coat the polydopamine layer. Wash with deionized water and ethanol, and dry in an oven at 40°C to obtain a magnetic MXene composite material with surface polydopamine functionalized.
[0056] Step 3: Weigh 1g of FS61 fluorocarbon compound and dissolve it in 100 mL of ultrapure water by ultrasonic stirring, and mix thoroughly to obtain a fluorocarbon compound solution for use. Weigh 0.5g of the surface polydopamine functionalized magnetic MXene composite material of step 2 in 10mL of ultrapure water, ultrasonicate for 5min to fully disperse the composite material to obtain the first dispersion, and then transfer the first dispersion to the above fluorocarbon compound solution, stir and react at 40°C for 3h. After the reaction is completed, separate it using an external magnetic field, wash it and vacuum dry it to obtain a fluorocarbon functionalized MXene-based composite material.
[0057] A fluorocarbon functionalized MXene-based composite material, wherein ferroferric oxide magnetic nanoparticles are uniformly attached to the outer surface of a MXene layered matrix and between layers to form a magnetic MXene composite structure, the surface of the magnetic MXene composite structure is coated with a polydopamine layer, the surface of the polydopamine layer is attached with a fluorocarbon compound, and the fluorocarbon compound is FS61.
[0058] Example 2
[0059] Referring to the preparation method of Example 1, the difference is that in step 1 of the preparation method, the amount of anhydrous ferric chloride is 3 g, the amount of anhydrous sodium acetate is 10 g, the amount of polyethylene glycol is 2 g, the amount of MXene layered matrix is 1 g, the reaction temperature of the solvothermal reaction is 200 ° C, and the reaction time is 10 h; in step 2, the amount of magnetic MXene composite material is 1 g, the amount of dopamine solid is 2 g, the pH of the Tris-HCl buffer solution is 8, the amount is 100 mL, and the reaction conditions are stirred at a water bath temperature of 37 ° C for 36 h; in step 3, 0.5 g FS61 fluorocarbon compound is weighed and dissolved in 80 mL of ultrapure water by ultrasonic stirring, and 1 g of the polydopamine functionalized magnetic nanocomposite prepared above is weighed and dissolved in 20 mL of ultrapure water, and the composite material is fully dispersed by ultrasonication for 10 min, and the stirring reaction time is 2 h.
[0060] Example 3
[0061] Refer to the preparation method of Example 1, except that in step 1, 2 g of anhydrous ferric chloride, 12 g of anhydrous sodium acetate, 3 g of polyethylene glycol and 3 g of MXene layered matrix are weighed and placed in a beaker.
[0062] Example 4
[0063] Refer to the preparation method of Example 1, except that in step 2, the amount of dopamine solid added is 0.1 g.
[0064] Example 5
[0065] The preparation method of Example 1 is referred to, except that in step 3, the amount of fluorocarbon compound added is 0.1 g.
[0066] Example 6
[0067] Referring to the preparation method of Example 1, the difference is that in step 3, the fluorocarbon compound is FS34. Referring to the composite material of Example 1, the fluorocarbon compound attached to the surface of the polydopamine layer is FS34.
[0068] Example 7
[0069] The preparation method of Example 1 is referred to, except that in step 1, the temperature of the solvent thermal reaction is 150°C.
[0070] Example 8
[0071] Refer to the preparation method of Example 1, except that in step 1, the solvent thermal reaction time is 5 hours.
[0072] Example 9
[0073] Refer to the preparation method of Example 1, except that in step 1, sodium citrate is used instead of anhydrous sodium acetate.
[0074] Example 10
[0075] Refer to the preparation method of Example 1, the difference is that in step 1, ethanol is used instead of ethylene glycol.
[0076] Embodiment 11
[0077] Referring to the preparation method of Example 1, the difference is that the process of preparing the magnetic MXene composite material in step 1 is not carried out, and commercially available ferrosoferric oxide magnetic nanoparticles are attached to the MXene layered matrix by wet stirring.
[0078] Example 12
[0079] Refer to the preparation method of Example 1, except that in step 2, the reaction is stirred at a water bath temperature of 4° C. for 72 hours and then adsorbed and separated by an external strong magnet.
[0080] Embodiment 13
[0081] Refer to the preparation method of Example 1, except that in step 2, the reaction is stirred at a water bath temperature of 40° C. for 10 h and then separated by adsorption using an external strong magnet.
[0082] Embodiment 14
[0083] The preparation method of Example 1 is referred to, except that in step 3, the temperature of the stirring reaction for attaching the fluorocarbon compound is 15°C.
[0084] Embodiment 15
[0085] The preparation method of Example 1 is referred to, except that in step 3, the stirring reaction time of the attached fluorocarbon compound is 0.2 h.
[0086] Example 16
[0087] The preparation method of Example 1 is referred to, except that, in step 3, 1 g of FS61 fluorocarbon compound and 0.5 g of the surface polydopamine functionalized magnetic MXene composite material of step 2 are weighed in 110 ml of ultrapure water, and after ultrasonic stirring and mixing, the mixture is stirred at 40° C. for 3 h. After the reaction is completed, the mixture is separated by an external magnetic field, washed and vacuum dried to obtain a fluorocarbon functionalized MXene-based composite material.
[0088] Comparative Example 1
[0089] Referring to the preparation method of Example 1, the difference is that step two and step three are not performed, and the magnetic MXene composite material is prepared only by step one, and the ferrosoferric oxide magnetic nanoparticles are attached to the interlayers of the MXene layered matrix and the outer surface of the MXene layered matrix.
[0090] Experimental example
[0091] Experimental Example 1
[0092] The fluorocarbon functionalized MXene-based composite materials of Examples 1 to 16 were subjected to scanning electron microscopy, element distribution point scanning, and energy dispersive x-ray (EDX) analysis. The distribution of magnetic nanoparticles in the fluorocarbon functionalized MXene-based composite materials of Examples 1 to 16 is shown in Table 1. Figure 1 This is a scanning electron microscope image of the fluorocarbon functionalized MXene-based composite material prepared in Example 1 of the present invention. The MXene layer structure can be clearly seen, and the magnetic nanoparticles are attached to the MXene layer, indicating that the material is successfully composited. A relatively rough coating layer can be clearly seen on the surface of the composite material, indicating that the polymer has successfully self-polymerized on the surface of the composite material. Figure 2 This is the element distribution diagram of the fluorocarbon functionalized MXene-based composite material prepared in Example 1 of the present invention. From the element distribution in the figure, it can be seen that the elements Fe, O, N, C, Ti, F and other elements contained in the composite material can be detected. Among them, the Ti element is mainly distributed on the surface of the sheet, further proving that the sheet is MXene, and the F element is evenly distributed on the surface of the composite material. The fluorocarbon compound is successfully attached to the material. The scanning electron microscope images and element distribution diagrams of the fluorocarbon functionalized MXene-based composite materials of Examples 2 to 16 are similar to Figure 1 and Figure 2 There is no significant difference.
[0093] Experimental Example 2
[0094] The fluorocarbon functionalized MXene-based composite materials prepared in Examples 1 to 16 were characterized by X-ray photoelectron spectroscopy (XPS) to verify the chemical composition of the materials and the chemical state of the related elements. Figure 3 shown. Figure 3The figure in the upper left corner is the elemental full scan spectrum, and the element absorption peaks correspond to the four elements F 1s, O (1s,2s), N 1s, and C 1s. The figure in the upper right corner is the C 1s high-resolution spectrum, and the binding energies of 284.5 eV, 285.8 eV, 286.2 eV and 290.8 eV correspond to the C−C / C−H, C−N / C−O, C=O and N−C=O bonds of the nanomaterials, respectively, indicating that polydopamine is successfully coated on the surface of the magnetic MXene composite material. The figure in the lower left corner is the O 1s high-resolution spectrum, and the characteristic peaks of C-Ti-O and C-Ti-OH appear, indicating that MXene is compounded in the composite material. The figure in the lower left corner is the F 1s high-resolution spectrum, and the characteristic peaks of the CF bond appear, indicating that fluorocarbon compounds are attached to the surface of the composite material. XPS results of fluorocarbon functionalized MXene-based composite materials of Examples 2 to 16 are characterized and Figure 1 and Figure 2 There is no significant difference.
[0095] Experimental Example 3
[0096] The hysteresis loops of the fluorocarbon functionalized MXene-based composite materials of Examples 1 to 16 and the magnetic MXene composite materials of Comparative Example 1 at room temperature were recorded by a vibrating sample magnetometer (VSM) to characterize the magnetic response intensity of the fluorocarbon functionalized MXene-based composite materials of Examples 1 to 16 and the magnetic MXene composite materials of Comparative Example 1. The specific detection conditions are to periodically change the direction of the magnetic field within the magnetic field range of ±2T, record the relationship between the sample magnetization intensity and the magnetic field intensity, and obtain the hysteresis loop. The magnetic response intensity of the fluorocarbon functionalized MXene-based composite materials of Examples 1 to 16 and the magnetic MXene composite materials of Comparative Example 1 is shown in Table 1.
[0097] Experimental Example 4
[0098] The main element contents of the fluorocarbon functionalized MXene-based composite materials of Examples 1 to 16 were scanned and calculated using a transmission electron microscope to obtain the main element contents. The fluorine element contents of the fluorocarbon functionalized MXene-based composite materials of Examples 1 to 16 were detected and shown in Table 1.
[0099] Experimental Example 5
[0100] The same mass of the fluorocarbon functionalized MXene-based composite materials of Examples 1 to 16 and the magnetic MXene composite material of Comparative Example 1 were used for plant virus RNA enrichment extraction and qPCR detection, respectively.
[0101] Accurately transfer 140uL of plant virus sample, add 560uL of lysis solution and 800uL of acidic extraction solution (NaCl 4M, dithiothreitol 50mM, PEG20%, pH5), incubate at room temperature for 10min, and obtain the incubation liquid. Then add fluorocarbon functionalized MXene-based composite material or magnetic MXene composite material to the incubation liquid, vortex mix and extract for 10min to obtain the second dispersion. After the second dispersion is separated by an external magnetic field, the fluorocarbon functionalized MXene-based composite material adsorbed with RNA is collected, and then 1mL of 75% ethanol is added to clean the composite material. Then, the RNA on the composite material is directly reverse transcribed into DNA according to the kit operation, and 5uL of the reverse transcribed composite material is taken, and primers and probes are added for qPCR amplification. The qPCR instrument was an AB7500 real-time fluorescence quantitative qPCR instrument, and the qPCR detection amplification conditions were as follows: the first stage: amplification at 95°C for 10 min, the second stage: amplification at 95°C for 10 s and at 60°C for 1 min, 45 cycles, and the fluorescence signal was collected during the 60°C period of the second stage to obtain the qPCR data graph. The Ct values of the qPCR detection of the fluorocarbon functionalized MXene-based composite materials of Examples 1 to 16 and the magnetic MXene composite material of Comparative Example 1 are shown in Table 1.
[0102] Experimental Example 6
[0103] Refer to Experimental Example 5, the difference is that the fluorocarbon functionalized MXene-based composite material of Example 1 with RNA adsorbed is collected, 1 mL of 75% ethanol is added to wash the composite material, and the fluorocarbon functionalized MXene-based composite material of Example 1 with RNA adsorbed is dispersed in ethanol, and a third dispersion is obtained after sufficient mixing. The third dispersion is separated by solid-liquid separation to obtain a solid phase, and the solid phase is fully mixed with Tris-HCl buffer at a pH of 8.5, and RNA is fully released from the fluorocarbon functionalized MXene-based composite material, and then an external magnetic field is performed to separate to obtain an RNA dispersion. Then, the RNA in the RNA dispersion is reverse transcribed into DNA according to the kit operation, 5uL of the reverse transcription product is taken, and primers and probes are added for qPCR amplification, and the Ct value of the qPCR detection is 32.
[0104] Table 1
[0105]
[0106] The fluorocarbon functionalized MXene-based composite material of Example 1 was subjected to Experimental Example 5 in which the RNA on the fluorocarbon functionalized MXene-based composite material was directly reverse transcribed and then qPCR detection, and Experimental Example 6 in which the RNA was released from the composite material and the RNA in the RNA dispersion was reverse transcribed and then qPCR detection was performed. The Ct value of the qPCR detection was smaller for the reverse transcription of the RNA in the RNA dispersion, and the reverse transcription after the RNA was desorbed, the reverse transcription was more sufficient, and the RNA detection accuracy was higher.
[0107] By comparing the embodiments and comparative examples, coating a polydopamine layer on the surface of the magnetic MXene composite structure and attaching a fluorocarbon compound on the surface of the polydopamine layer can significantly improve the ability of the composite material to enrich and extract plant virus RNA.
[0108] Comparing Example 1 with Example 3, in the preparation process of the magnetic MXene composite material, anhydrous ferric chloride, anhydrous sodium acetate, polyethylene glycol and MXene layered matrix are mixed in a mass ratio of (1-3): (2-5): 1: (0.5-3), which is more conducive to the uniform attachment of magnetic nanoparticles to the outer surface and between the layers of the MXene layered matrix, thereby improving the magnetic properties of the composite material, increasing the fluorine content of the composite material, and improving the ability to enrich and extract plant virus RNA; Comparing Example 1 with Example 4, the mass ratio of the magnetic MXene composite material to dopamine is 1: (0.5-5), which is more conducive to increasing the fluorine content of the composite material, improving the enrichment and extraction of plant virus RNA. The ability to extract plant viral RNA, comparing Example 1 and Example 5, the process of attaching fluorocarbon compounds, the fluorocarbon compound and the magnetic MXene composite material functionalized with surface polydopamine are mixed in a mass ratio of 1:0.1-3, which is more conducive to increasing the fluorine content of the composite material and improving the ability to enrich and extract plant viral RNA, comparing Example 1 and Example 6, the fluorocarbon compound is FS61, which is more conducive to improving the ability to enrich and extract plant viral RNA, comparing Examples 1, 7, 8 and 9, the preparation process of the magnetic MXene composite material, the reaction temperature of the solvent thermal reaction is not less than 160°C, the reaction time is not less than 6h, and the weak acid and strong base salt is no Sodium acetate in water is more conducive to improving the magnetic properties and fluorine content of the composite material, and improving the ability to enrich and extract plant virus RNA. Comparing Examples 1 and 10, the preparation process of the magnetic MXene composite material uses polyols such as ethylene glycol, which is more conducive to improving the magnetic properties of the composite material, increasing the fluorine content of the composite material, and improving the ability to enrich and extract plant virus RNA. Comparing Examples 1 and 11, the solvothermal reaction prepares magnetic nanoparticles while attaching the magnetic nanoparticles to the MXene layered matrix, which is more conducive to the uniform attachment of magnetic nanoparticles to the outer surface and between the layers of the MXene layered matrix, improving the magnetic properties of the composite material, and increasing the fluorine content of the composite material. Improve the ability to enrich and extract plant viral RNA. Comparing Example 1 and Example 12, the temperature of dopamine self-polymerization coating on the surface of the magnetic MXene composite material is not less than 20°C, which is more conducive to increasing the fluorine content of the composite material and improving the ability to enrich and extract plant viral RNA. Comparing Example 1 and Example 13, the time of dopamine self-polymerization coating on the surface of the magnetic MXene composite material is not less than 24h, which is more conducive to increasing the fluorine content of the composite material and improving the ability to enrich and extract plant viral RNA. Comparing Examples 1, 14 and 15, during the process of attaching the fluorocarbon compound, the stirring reaction temperature is not less than 20°C and the time is not less than 0.5h, which is more conducive to increasing the fluorine content of the composite material and improving the ability to enrich and extract plant virus RNA. Compared with Example 1 and Example 16, when attaching fluorocarbon compounds, the dispersion of the magnetic MXene composite material functionalized with surface polydopamine is added to the fluorocarbon solution to mix the magnetic MXene composite material functionalized with surface polydopamine and the fluorocarbon in water, which is more conducive to increasing the fluorine content of the composite material and improving the ability to enrich and extract plant virus RNA. .
[0109] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various technical features in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.
Claims
1. A fluorocarbon functionalized MXene-based composite material for plant virus RNA detection, characterized in that: The invention comprises a magnetic MXene composite structure, a polydopamine layer coated on the surface of the magnetic MXene composite structure and a fluorocarbon compound attached to the surface of the polydopamine layer. The magnetic MXene composite structure is constituted by a MXene layered matrix and magnetic nanoparticles attached to the MXene layered matrix. The magnetic nanoparticles are attached between the lamellae of the MXene layered matrix and / or on the outer surface of the MXene layered matrix. The fluorocarbon compound comprises a surfactant having a fluorocarbon chain as a non-polar group.
2. The fluorocarbon functionalized MXene-based composite material according to claim 1, characterized in that: The magnetic nanoparticles are uniformly attached to the outer surface and between the layers of the MXene layered matrix.
3. The fluorocarbon functionalized MXene-based composite material according to claim 1, characterized in that: The magnetic response intensity of the fluorocarbon functionalized MXene-based composite material is 10 emu / g-50 emu / g; and / or, based on the total weight of the fluorocarbon functionalized MXene-based composite material, the weight proportion of fluorine element is 0.5wt%-10wt%.
4. The fluorocarbon functionalized MXene-based composite material according to claim 1, characterized in that: The fluorocarbon compound is selected from at least one of FS34, FS50, FS61, FS3000 and FS3100; the magnetic nanoparticles are selected from at least one of ferroferric oxide nanoparticles and spinel ferrite nanoparticles.
5. The fluorocarbon functionalized MXene-based composite material according to claim 4, characterized in that: The fluorocarbon compound includes FS61, the MXene layered matrix includes titanium carbide, and the magnetic nanoparticles include ferrosoferric oxide nanoparticles.
6. A method for preparing a fluorocarbon functionalized MXene-based composite material according to any one of claims 1 to 5, characterized in that: include: Magnetic nanoparticles are attached to a MXene layered matrix to obtain a magnetic MXene composite material, a polydopamine layer is coated on the surface of the magnetic MXene composite material to obtain a magnetic MXene composite material with surface polydopamine functionalization, a fluorocarbon compound is attached to the surface of the polydopamine layer to obtain the fluorocarbon functionalized MXene-based composite material, and the fluorocarbon compound is a surfactant with a fluorocarbon chain as a non-polar group.
7. The preparation method according to claim 6, characterized in that: The preparation of the magnetic MXene composite material comprises: mixing a metal salt, a weak acid and strong base salt, a polyol polymer and a MXene layered matrix in a polyol, and obtaining the magnetic MXene composite material through a solvothermal reaction.
8. The preparation method according to claim 7, characterized in that: The preparation of the magnetic MXene composite material also includes: the metal salt is anhydrous ferric chloride, the weak acid and strong base salt is anhydrous sodium acetate, the polyol polymer is polyethylene glycol, and the polyol is ethylene glycol; anhydrous ferric chloride, anhydrous sodium acetate, polyethylene glycol and MXene layered matrix are mixed in a mass ratio of (1-3): (2-5): 1: (0.5-3), and 10mL-35mL of ethylene glycol is used for each gram of anhydrous ferric chloride; The reaction temperature of the solvent thermal reaction is 160° C.-220° C., and the reaction time is 6 h-12 h.
9. The preparation method according to claim 6, characterized in that: The preparation of the magnetic MXene composite material with surface polydopamine functionalization includes: mixing the magnetic MXene composite material and dopamine in a buffer solution, stirring and reacting at a temperature of 20° C. to 50° C. for 24 h to 72 h, and allowing dopamine to self-polymerize on the surface of the magnetic MXene composite material to coat a polydopamine layer, thereby obtaining the magnetic MXene composite material with surface polydopamine functionalization; The pH of the buffer solution is 7-9, the magnetic MXene composite material and dopamine are mixed in a mass ratio of 1:(0.5-5), and the buffer solution is a Tris-HCl buffer.
10. The preparation method according to claim 6, characterized in that: The process of attaching the fluorocarbon compound includes: mixing the surface polydopamine functionalized magnetic MXene composite material and the fluorocarbon compound in water, stirring and reacting at a temperature of 20°C to 50°C for 0.5h-5h; the fluorocarbon compound and the surface polydopamine functionalized magnetic MXene composite material are mixed in a mass ratio of 1: (0.1-3).
11. The preparation method according to claim 10, characterized in that: The fluorocarbon compound is dissolved in water to obtain a fluorocarbon compound solution, the surface polydopamine functionalized magnetic MXene composite material is dispersed in water to obtain a first dispersion, and the first dispersion is added to the fluorocarbon compound solution to mix the surface polydopamine functionalized magnetic MXene composite material and the fluorocarbon compound in water.
12. A method for detecting plant viral RNA, characterized in that: The plant virus sample to be detected is incubated in a lysis solution and an acidic extraction solution at room temperature to obtain an incubated liquid, and the fluorocarbon functionalized MXene-based composite material described in any one of claims 1 to 5 and / or the fluorocarbon functionalized MXene-based composite material prepared by the preparation method described in any one of claims 6 to 11 is added to the incubated liquid, and a second dispersion is obtained after sufficient mixing. After the second dispersion is separated by an external magnetic field, a fluorocarbon functionalized MXene-based composite material adsorbed with RNA is obtained, and the RNA is reverse transcribed into DNA, and PCR amplification is performed after reverse transcription. The reverse transcription of RNA into DNA is to directly reverse transcribe the RNA on the fluorocarbon functionalized MXene-based composite material, or to release the RNA from the fluorocarbon functionalized MXene-based composite material to obtain an RNA dispersion, and the RNA in the RNA dispersion is reverse transcribed.
13. The detection method according to claim 12, characterized in that: The pH of the acidic extract is 3-7. The acidic extract contains NaCl, dithiothreitol and PEG, wherein the concentration of NaCl is 0.5mol / L-6mol / L, the concentration of dithiothreitol is 10mmol / L-200mmol / L, and the volume fraction of PEG is 5%-50%.
14. The detection method according to claim 12, characterized in that: The fluorocarbon functionalized MXene-based composite material adsorbed with RNA is dispersed in ethanol, and a third dispersion is obtained after sufficient mixing. The third dispersion is separated into a solid phase by solid-liquid separation. The solid phase is fully mixed with a Tris-HCl buffer having a pH of 8 to 9, and then separated by an external magnetic field to obtain the RNA dispersion.
Citation Information
Patent Citations
Method for detecting prostatic cancer exosome microRNA by light-mediated phase change sol microdroplet digital PCR technology
CN114703285A
Neural stem cell culture and detection integrated platform based on MXene-Fe3O4 and application thereof
CN115558643A